Why is there still Rabies in the world? An emerging microbial and global health threat (2010)
This review reports on why is there still rabies in the world?-an emerging microbial and global health threat. Rabies remains an important public health issue in the world. While rabies has been controlled throughout most of the developed world, it remains a significant burden in developing countries, particularly in Africa and Asia. Although industrialized countries have been able to contain recent outbreaks, many resource-limited and transitioning countries have not been able to react adequately. Although, a vaccinepreventable disease, the annual number of human deaths caused by rabies is estimated to be 35,000 per year, mostly in Africa, Asia and Latin America. Though, dogs have been identified as being primarily responsible for the transmission of rabies in human and other domestic animals, known pathogenesis and available data suggest that all or nearly all cases of human rabies attributable to bats were transmitted by bat bites that were minimized or unrecognized by the patients. One of the key for controlling rabies is to focus on the animal reservoir. The high incidence of rabies in some country led to numerous concerns attributed to a potential carrier-dog phenomenon, undocumented transmission of rabies virus from wildlife to dogs, counterfeit vaccines, vaccine mismatching and seroconversion testing in patients after their completion of postexposure prophylaxis. However, the number of reported human rabies cases, particularly in Africa, greatly underestimates the true effects of the disease. Contributing factors include failure to seek treatment at healthcare facilities, failure to make a laboratory diagnosis and failure to report the disease. The disconnection between human and dog rabies in developing world reflects a lack of awareness of the concept of one medicine, or health without regard to species, in approaches to rabies control in the public health system. Another factor contributing to the endemicity of rabies in the world could be attributed to low vaccine coverage. Although there are many factors that contribute to the epidemic or endemic nature of rabies in the world, the single most important factor is the failure to immunize domestic dogs, which transmit rabies to humans. Regional and local disease resurgence occurs, due in part to a combination of political and economic instability, environmental perturbations and shifting government priorities. Indeed rabies is a widely distributed zoonotic disease of major public-health importance and an emerging as well as re-emerging microbial and global health threat but a preventable problem. Surveillance strategies for rabies and other rabies-ralated viruses in the world, particularly Africa must be improved to better understand the epidemiology of this virus and to make informed decisions on future vaccine strategies.